Modified acrylate composite grouting material, preparation method thereof and grouting method
Patent Information
- Application Number
- CN202611353764.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-20
AI Technical Summary
综上,现有丙烯酸酯类灌浆材料仍存在干燥体积稳定性不足、耐温抗盐和耐冲刷性能有限、施工调控环节较多、安全环保性不足以及适用场景受限等技术问题
本发明提供的改性丙烯酸酯复合灌浆材料,由基料组分M与引发交联组分N复配而成。具体而言:(1)改性丙烯酸酯单体混合物与多官能团复合交联体系共同形成交联网络,有利于提高凝胶体结构致密性及固砂体力学稳定性;(2)焦亚硫酸钠与抗坏血酸组成的环保型促进剂能够避免使用有毒有机促进剂,并可通过复合引发剂用量和双组分混合比调节凝胶时间;(3)失水山梨醇单油酸酯与聚氧乙烯聚氧丙烯醚组成的复合亲水亲油调节剂,有利于兼顾建筑防渗所需的低渗透性能和油田工况下的选择性堵水性能;(4)纳米二氧化硅、改性膨润土与水性弹性乳液协同,有利于提高固结体的干燥体积保持能力和耐冲刷稳定性。经检测,采用该灌浆材料进行灌注,混合浆液初始黏度为55.8~88.4 mPa·s,固砂体抗压强度为653.9~786.3 kPa,干燥体积保持率为87.6%~92.7%(对应干燥体积收缩率为7.3%~12.4%),渗透系数为2.5×10-9~4.1×10-9cm/s,堵水率为93.2%~99.1%,堵油率为4.5%~9.5%,耐冲刷倍数为52~78 PV,大鼠经口LD50均大于10000 mg/kg。综上,该改性丙烯酸酯复合灌浆材料在不同用量点和灌浆场景下具有较好的综合性能,能够改善现有丙烯酸酯类灌浆材料在干燥体积稳定性、耐温抗盐性能、耐冲刷性能、施工调控便利性、安全环保性以及多场景适用性方面的不足。
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of grouting materials for engineering seepage prevention, plugging and ground reinforcement, specifically involving modified acrylic composite grouting materials and their preparation and grouting methods. Background Technology
[0002] Grouting materials are indispensable key materials in engineering fields such as building waterproofing, ground reinforcement, and oil and gas field management. With their excellent penetration, consolidation and sealing properties, they are widely used in various engineering scenarios such as building seepage prevention, tunnel support and oilfield formation water plugging.
[0003] Among numerous grouting material systems, acrylic grouting materials have gradually become one of the most widely used materials in the industry due to their advantages such as low grout viscosity, strong permeability, and adjustable gelation speed. Based on differences in actual application scenarios and functional positioning, existing acrylic grouting materials mainly include acrylate anti-seepage grouting materials suitable for building engineering and selective water-blocking polymer grouting materials used in oilfields. However, existing products still struggle to simultaneously meet the diverse and complex engineering needs. Specifically, acrylate grouting materials for building anti-seepage are prone to volume shrinkage and re-leakage in dry environments, and some materials lack sufficient temperature and salt resistance, requiring the addition of retarders to control gelation time. While selective water-blocking polymer materials for oilfields can achieve selective sealing, the strength of the solidified sand and its erosion resistance still have room for improvement. Furthermore, some existing formulations use a single crosslinking system, resulting in insufficient compatibility between initiators and accelerators, and an insufficiently dense gel network structure; there is also a lack of synergistic compatibility between hydrophilic and oleophilic components, making it difficult to simultaneously meet the requirements of building anti-seepage and selective water-blocking in oilfields. Some formulations also use toxic organic accelerators, posing risks to construction safety and the environment. In summary, existing acrylic grouting materials still suffer from technical problems such as insufficient drying volume stability, limited temperature, salt, and erosion resistance, numerous construction control steps, inadequate safety and environmental friendliness, and limited applicability. Summary of the Invention
[0004] In order to overcome the shortcomings of the prior art, the present invention aims to provide a modified acrylic composite grouting material and its preparation and grouting methods, so as to improve the shortcomings of existing acrylic grouting materials in terms of dry volume stability, temperature and salt resistance, erosion resistance, construction control convenience, safety and environmental protection, and applicability to multiple scenarios.
[0005] To achieve the above objectives, the present invention employs the following technical solution: The first aspect of this invention discloses a modified acrylic composite grouting material, comprising a base component M and a crosslinking initiator N; by weight, The base component M includes: 28-54 parts of modified acrylate monomer mixture, 3.2-8.9 parts of composite hydrophilic and lipophilic modifier, 0.6-4.1 parts of environmentally friendly accelerator, 5.7-12.5 parts of functional inorganic filler, 32.8-56.9 parts of solvent, 1.1-2.7 parts of co-solvent and 0.2-0.7 parts of anti-settling agent; The cross-linking initiating component N includes: 1.5~10.5 parts of composite cross-linking agent, 0.7~3.9 parts of composite initiator, 8.5~19.6 parts of aqueous elastic emulsion, 0.1~0.5 parts of pH adjuster, 68.9~82.3 parts of solvent and 0.05~0.2 parts of defoamer; The modified acrylate monomer mixture comprises 20-35 parts zinc acrylate, 5-10 parts aluminum methacrylate, 2-6 parts hydroxypropyl acrylate, and 1-3 parts octadecyl methacrylate; the composite hydrophilic and lipophilic regulator comprises sorbitan monooleate and polyoxyethylene polyoxypropylene ether in a mass ratio of 2:1; the environmentally friendly accelerator comprises sodium metabisulfite and ascorbic acid in a mass ratio of (3-5):1; the functional inorganic filler comprises nano-silica and modified bentonite in a mass ratio of 1:2; the composite crosslinking agent comprises 4-7 parts pentaerythritol triallyl ether, 2-5 parts polyethylene glycol diacrylate, and 1-2 parts N-hydroxymethylacrylamide; and the composite initiator comprises ammonium persulfate and azobisisobutylamidine hydrochloride in a mass ratio of 4:1.
[0006] Preferably, the modified bentonite is quaternary ammonium salt modified bentonite.
[0007] Preferably, the solvent is water.
[0008] Preferably, the co-solvent is selected from one or more of ethylene glycol monobutyl ether, propylene glycol methyl ether, and diethylene glycol monobutyl ether.
[0009] Preferably, the anti-settling agent is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, and xanthan gum.
[0010] Preferably, the aqueous elastic emulsion is selected from one or more of acrylate-butadiene copolymer emulsion, pure acrylic emulsion, styrene-acrylic emulsion, and carboxylated styrene-butadiene emulsion.
[0011] Preferably, the pH adjuster is selected from one or more of sodium bicarbonate, potassium bicarbonate, and sodium carbonate.
[0012] Preferably, the defoamer is selected from one or more of polydimethylsiloxane and polyether-modified siloxane.
[0013] In a second aspect, the present invention discloses a method for preparing a modified acrylate composite grouting material. 20-35 parts of zinc acrylate, 5-10 parts of aluminum methacrylate, 2-6 parts of hydroxypropyl acrylate, and 1-3 parts of octadecyl methacrylate are mixed to obtain a modified acrylate monomer mixture. Sodium metabisulfite and ascorbic acid are mixed at a mass ratio of (3-5):1 to obtain an environmentally friendly accelerator. Sieve-finished nano-silica and modified bentonite are mixed at a mass ratio of 1:2 to obtain a functional inorganic filler. Under stirring, a co-solvent, the modified acrylate monomer mixture, a composite hydrophilic-lipophilic regulator, an environmentally friendly accelerator, a functional inorganic filler, and an anti-settling agent are sequentially dissolved in a solvent, ground, and filtered to obtain the base material component M. 4-7 parts of pentaerythritol triallyl ether, 2-5 parts of polyethylene glycol diacrylate, and 1-2 parts of N-hydroxymethylacrylamide were mixed to obtain a composite crosslinking agent; ammonium persulfate and azobisisobutylamidine hydrochloride were mixed at a mass ratio of 4:1 to obtain a composite initiator; under stirring, a pH adjuster, a composite crosslinking agent, an aqueous elastic emulsion, a composite initiator, and an antifoaming agent were dissolved in a solvent in sequence, filtered, and the initiating crosslinking component N was obtained.
[0014] In a third aspect, the present invention discloses a grouting method for a modified acrylic composite grouting material, wherein the base component M and the crosslinking initiator N are mixed at a mass ratio of 1:(0.8~1.2) and then injected into the grouting location using a staged pressurization method.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The modified acrylate composite grouting material provided by this invention is composed of a base component M and an initiating crosslinking component N. Specifically: (1) The modified acrylate monomer mixture and the multifunctional group composite crosslinking system together form a crosslinking network, which is beneficial to improving the density of the gel structure and the mechanical stability of the solid sand; (2) The environmentally friendly accelerator composed of sodium metabisulfite and ascorbic acid can avoid the use of toxic organic accelerators, and the gelation time can be adjusted by the amount of composite initiator and the mixing ratio of the two components; (3) The composite hydrophilic and oleophilic regulator composed of sorbitan monooleate and polyoxyethylene polyoxypropylene ether is beneficial to take into account both the low permeability required for building seepage prevention and the selective water shut-off performance under oilfield conditions; (4) The synergistic effect of nano silica, modified bentonite and water-based elastic emulsion is beneficial to improve the dry volume retention capacity and erosion resistance of the solidified body. Testing revealed that when this grouting material was used for injection, the initial viscosity of the mixed grout was 55.8–88.4 mPa·s, the compressive strength of the solidified sand was 653.9–786.3 kPa, the dry volume retention rate was 87.6%–92.7% (corresponding to a dry volume shrinkage rate of 7.3%–12.4%), and the permeability coefficient was 2.5 × 10⁻⁶. -9 ~4.1×10 -9cm / s, water blocking rate 93.2%~99.1%, oil blocking rate 4.5%~9.5%, scour resistance ratio 52~78 PV, oral LD50 in rats 50 All values are greater than 10,000 mg / kg. In summary, this modified acrylic composite grouting material exhibits good comprehensive performance at different dosage points and grouting scenarios, and can improve the shortcomings of existing acrylic grouting materials in terms of dry volume stability, temperature and salt resistance, erosion resistance, ease of construction control, safety and environmental protection, and applicability to multiple scenarios. Detailed Implementation
[0016] To enable those skilled in the art to understand the features and effects of the present invention, the following description and definitions are only general descriptions of the terms and expressions mentioned in the specification. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0017] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0018] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0019] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0020] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0021] In this paper, a dual-liquid grouting pump is used to achieve dynamic mixing and continuous grouting of modified acrylic composite grouting material. Parameters such as mixing ratio, grouting pressure, and gel time can be precisely controlled according to the engineering scenario, and no retarder or setting aid is required, making construction highly convenient.
[0022] In this article, the weight parts referred to are relative parts used to determine the relative mass relationship of each raw material. Unless otherwise stated, it is not required that the sum of the weight parts of each item in the same component equals 100 parts.
[0023] This invention provides a modified acrylic composite grouting material, which is a two-component, ready-to-use liquid system, comprising: The base component M is the main phase of the grouting material, which provides monomers, promotes the reaction, and regulates the system compatibility and basic mechanical properties. By weight, the raw material composition is: 28~54 parts modified acrylate monomer mixture, 3.2~8.9 parts composite hydrophilic and lipophilic regulator, 0.6~4.1 parts environmentally friendly accelerator, 5.7~12.5 parts functional inorganic filler, 32.8~56.9 parts solvent, 1.1~2.7 parts co-solvent and 0.2~0.7 parts anti-settling agent; The modified acrylate monomer mixture comprises 20-35 parts zinc acrylate, 5-10 parts aluminum methacrylate, 2-6 parts hydroxypropyl acrylate, and 1-3 parts octadecyl methacrylate; the composite hydrophilic and lipophilic regulator comprises sorbitan monooleate and polyoxyethylene polyoxypropylene ether in a mass ratio of 2:1; the environmentally friendly accelerator comprises sodium metabisulfite and ascorbic acid in a mass ratio of (3-5):1; the functional inorganic filler comprises nano-silica and modified bentonite in a mass ratio of 1:2, wherein the modified bentonite is preferably quaternary ammonium salt modified bentonite; the solvent is water, preferably deionized water; the co-solvent is selected from one or more of ethylene glycol monobutyl ether, propylene glycol methyl ether, and diethylene glycol monobutyl ether, preferably ethylene glycol monobutyl ether; the anti-settling agent is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, and xanthan gum, preferably hydroxyethyl cellulose.
[0024] The initiating crosslinking component N is the reaction phase of the grouting material, which plays a role in providing free radicals, constructing a three-dimensional network structure, improving the system's elasticity and reducing shrinkage. By weight, the raw material composition is: 1.5~10.5 parts composite crosslinking agent, 0.7~3.9 parts composite initiator, 8.5~19.6 parts aqueous elastic emulsion, 0.1~0.5 parts pH adjuster, 68.9~82.3 parts solvent and 0.05~0.2 parts defoamer; The composite crosslinking agent comprises 4-7 parts pentaerythritol triallyl ether, 2-5 parts polyethylene glycol diacrylate, and 1-2 parts N-hydroxymethylacrylamide; the composite initiator comprises ammonium persulfate and azobisisobutylamidine hydrochloride in a mass ratio of 4:1; the aqueous elastic emulsion is selected from one or more of acrylate-butadiene copolymer emulsion, pure acrylic emulsion, styrene-acrylic emulsion, and carboxylated styrene-butadiene emulsion, preferably acrylate-butadiene copolymer emulsion; the pH adjuster is selected from one or more of sodium bicarbonate, potassium bicarbonate, and sodium carbonate, preferably sodium bicarbonate; the defoamer is selected from one or more of polydimethylsiloxane and polyether-modified siloxane, preferably polydimethylsiloxane; the solvent is water, preferably deionized water.
[0025] This invention also provides a method for preparing modified acrylic composite grouting material, comprising the following steps: I. Preparation of base component M 1. Preparation of modified acrylate monomer mixture: 20-35 parts of zinc acrylate, 5-10 parts of aluminum methacrylate, 2-6 parts of hydroxypropyl acrylate and 1-3 parts of octadecyl methacrylate are mixed at a speed of 200-250 r / min, heated to 45±2℃, and stirred continuously for 25-30 min until completely dissolved. The mixture is then cooled to 25±5℃ to obtain the modified acrylate monomer mixture.
[0026] 2. Compounding of environmentally friendly accelerator: Mix the sieved sodium metabisulfite and ascorbic acid at a mass ratio of (3~5):1 until the two solids are completely homogeneous to obtain the environmentally friendly accelerator.
[0027] 3. Compounding of functional inorganic fillers: The sieved nano-silica and modified bentonite are mixed at a mass ratio of 1:2 to obtain functional inorganic fillers.
[0028] 4. Preparation of base component M: Under stirring, 1.1~2.7 parts of co-solvent, 28~54 parts of modified acrylate monomer mixture, 3.2~8.9 parts of composite hydrophilic and lipophilic regulator, 0.6~4.1 parts of environmentally friendly accelerator, 5.7~12.5 parts of functional inorganic filler and 0.2~0.7 parts of anti-settling agent are dissolved in 32.8~56.9 parts of solvent in sequence, ground until the particle size of the system is ≤50 μm, cooled to 25±5℃, filtered, and the base component M is obtained; In the above mixing process, the first ingredient is completely dissolved before the second ingredient is added.
[0029] II. Preparation of Crosslinking Component N 1. Preparation of composite crosslinking agent: Mix 4-7 parts of pentaerythritol triallyl ether, 2-5 parts of polyethylene glycol diacrylate and 1-2 parts of N-hydroxymethylacrylamide at 25±5℃ until the three raw materials are completely miscible to obtain the composite crosslinking agent.
[0030] 2. Compounding of composite initiator: The sieved ammonium persulfate and azobisisobutylamidine hydrochloride are mixed at a mass ratio of 4:1 to obtain the composite initiator.
[0031] 3. Preparation of initiating crosslinking component N: Under stirring, 0.1~0.5 parts of pH adjuster, 1.5~10.5 parts of composite crosslinking agent, 8.5~19.6 parts of aqueous elastic emulsion, 0.7~3.9 parts of composite initiator and 0.05~0.2 parts of defoamer are dissolved in 68.9~82.3 parts of solvent in sequence, filtered, and initiating crosslinking component N is obtained; In the above mixing process, the first raw material is completely dissolved before the second raw material is added; after adding the pH adjuster, the pH value of the system is 7.5~8.5; the composite initiator is added in portions, preferably 1 / 3 of the composite initiator is added every 3 minutes.
[0032] The above-mentioned base material component M and crosslinking initiator component N are prepared independently and stored in a sealed container. During construction, they are dynamically mixed by a dual-liquid grouting pump at a mass ratio of 1:(0.8~1.2) and then injected.
[0033] This invention also provides a grouting method based on modified acrylate composite grouting material, comprising the following steps: 1. Dynamic mixing Connect the dual-liquid grouting pump to the base material component M and the initiating crosslinking component N respectively. Set the mass ratio of the grouting pump to 1:(0.8~1.2), that is, when the delivery rate of base material component M is 10 kg / min, the delivery rate of initiating crosslinking component N is 8~12 kg / min. Set the stirring speed to 800~1000 r / min. After rapid and uniform mixing, the grouting liquid is obtained.
[0034] 2. Staged Injection The grouting fluid mixed in step 1 is delivered to the location to be treated through a high-pressure grouting pipe. The grouting pressure is adjusted according to the engineering scenario (building seepage prevention and plugging / oilfield profile control and water shut-off / rock and soil reinforcement). A staged pressure increase method is used for grouting to avoid sudden pressure increases that could lead to crack expansion and formation disturbance. Specific parameters are as follows: Building crack sealing (crack width 0.1~5 mm): Initial injection pressure 0.3 MPa, maintain for 5 min. If there is no leakage of grout, gradually increase the pressure at a rate of 0.1 MPa / 5 min, with the maximum pressure not exceeding 0.8 MPa. Stop injection when the crack is filled with grout and slight grout overflow appears on the surface. Soil and rock reinforcement (porosity 10%~30%): Initial grouting pressure 0.5 MPa, maintain for 10 min, after no grout leakage, gradually increase the pressure, with a maximum pressure of 1.2 MPa, until the grout penetration radius in the soil and rock reaches the design requirements; Oilfield profile control and water shut-off (formation temperature 40~130℃, salinity 1000~100000 mg / L): Initial injection pressure 0.8 MPa, adjusted according to formation permeability. When permeability ≥100 mD, increase pressure to 1.5 MPa; when permeability <100 mD, control pressure at 1.0~1.2 MPa. Slug injection is used, with each slug injecting 5~10 m³. 3 Perfuse 3-5 segments at 30-minute intervals.
[0035] 3. Gel time control The gel time of the slurry of this invention can be adjusted by combining the amount of composite initiator and the mixing ratio of the two components. Let the mass ratio of the base component M to the initiating crosslinking component N be 1:r, and the amount of composite initiator in the initiating crosslinking component N be dN. Then, its relative effective amount in the mixing system is proportional to dN×r / (1+r). If it is necessary to maintain a similar amount to the target amount d1 when mixing at a mass ratio of 1:1, the initial dosage can be determined according to dN=d1×(1+r) / (2r), and calibrated by a small-scale test before construction. According to this relationship, when r=0.8, the initial dosages for slow setting, medium setting, and fast setting are 0.79~1.69 parts, 1.80~3.15 parts, and 3.26~3.90 parts, respectively; when r=1.2, the corresponding initial dosages for slow setting, medium setting, and fast setting are 0.70~1.38 parts, 1.47~2.57 parts, and 2.66~3.58 parts, respectively. When r decreases, the relative amount of initiator in the mixture decreases, and the gel time tends to increase, making it suitable for longer delivery distances or full penetration; when r increases, the gel time tends to decrease, making it suitable for rapid leak plugging with water or sealing of high-permeability water layers. The following are the measured correlations under the conditions of r=1.0 and 25℃: The dosage of the composite initiator is 0.7~1.5 parts: the gelation time is 3~5 min at room temperature (25℃), which is suitable for grouting large cracks and large pores, ensuring full penetration of the grout; The dosage of the composite initiator is 1.6~2.8 parts; the gelation time is 1~3 min at room temperature (25℃), which is suitable for reinforcement of medium-sized cracks and conventional soil and rock masses. The dosage of the composite initiator is 2.9~3.9 parts: the gelation time is 30 s~1 min at room temperature (25℃), which is suitable for rapid plugging of leaks with water and sealing of high-permeability water layers in oil fields.
[0036] 4. Post-construction maintenance requirements After the grout injection is completed, natural curing will be carried out according to the engineering scenario, without the need for additional heating or pressurization. The curing requirements are as follows: Building crack sealing: The ambient temperature for curing is 5~35℃, the humidity is ≥50%, the curing time is ≥24 hours, and during the curing period, the grouting area should be protected from mechanical impact and water spray. Soil and rock reinforcement: curing time ≥ 48 h, during which excavation, compaction and other operations are prohibited in the reinforcement area; Oilfield profile control and water shut-off: utilize the formation's own temperature (40~130℃) for curing, with a curing time of ≥72 hours. After curing, normal water injection and oil production operations can be resumed in the oilfield.
[0037] 5. Key Points of Process Quality Control To ensure the reproducibility of the technical solution and the performance stability of the grouting material, the following quality control points must be strictly followed during preparation and construction. All tests must be conducted on-site immediately, and if any test fails, the process parameters must be adjusted immediately: Quality control of base component M: At room temperature (25℃), viscosity is controlled at 80~120 mPa·s (rotational viscometer, 60 r / min), particle size ≤50 μm, pH value is 6.5~7.5, and there is no stratification or precipitation; Quality control of crosslinking component N: At room temperature (25℃), viscosity is controlled at 30~50 mPa·s (rotational viscometer, 60r / min), pH value is 7.5~8.5, no floating oil or bubbles, and initiator activity ≥95%; Quality control of the mixed slurry: After the two components are mixed, the viscosity is controlled at 50~90 mPa·s (rotational viscometer, 60 r / min) at room temperature (25℃), the gelation time deviation is ≤±10%, and there is no phase separation or precipitation; Quality control during construction: grouting pressure deviation ≤ ±0.05 MPa, mixing ratio deviation ≤ ±5%, grout flow rate at the grouting pipe outlet remains constant, with no interruption or backflow.
[0038] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading this description, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined in this application.
[0039] The following examples use conventional instruments and equipment in the art; experimental conditions not specified are performed according to standard conditions. To ensure the availability of raw materials and the substitutability between products from different sources, each core raw material is determined according to its chemical name and verifiable specifications, without being limited to a specific manufacturer or product number: the purity of zinc acrylate and aluminum methacrylate is not less than 95%, the purity of hydroxypropyl acrylate and octadecyl methacrylate is not less than 98%; the purity of pentaerythritol triallyl ether is not less than 95%, the number average molecular weight of polyethylene glycol diacrylate is 600 and the purity is not less than 98%, the purity of N-hydroxymethylacrylamide is not less than 98%; the HLB value of sorbitan monooleate is 4.3±1.0, the number average molecular weight of polyoxyethylene polyoxypropylene ether is 3000~5000 and the HLB value is 12~16; the D of nano silica... 50 It has a wavelength of 25 nm and a specific surface area of 150~250 m². 2 / g, the fineness of quaternary ammonium salt modified bentonite is 200 mesh, and the moisture content is not higher than 3%; the purity of sodium metabisulfite, ascorbic acid, ammonium persulfate, and azobisisobutylamidine hydrochloride is not less than 98%; the weight average molecular weight of hydroxyethyl cellulose is 150,000, and its 2% aqueous solution has a viscosity of 1500~2500 mPa·s at 25℃; the solid content of acrylate-butadiene copolymer emulsion is 45.0%, the glass transition temperature is -22℃, the average particle size is 200 nm, and the pH value is 8.0; the viscosity of polydimethylsiloxane at 25℃ is 100~200 mPa·s. Commercially available products that meet the above specifications can be used directly. Solid raw materials should be sieved through a 120-mesh standard sieve for 5 minutes and then sealed before use. Liquid raw materials should be stirred at 500 r / min for 10 minutes before use; if stratification occurs, they should be stirred in a water bath at 40±2℃ until homogeneous and then cooled before use. Crosslinking agents and initiators should be stored separately in sealed containers and mixed immediately before use. In this specification and examples, unless otherwise stated, "%" indicates mass percentage, "parts" indicates parts by weight, and ratio indicates mass proportion.
[0040] Example 1 I. Preparation of Modified Acrylic Composite Grouting Material 1. Preparation of base component M 1) Preparation of modified acrylate monomer mixture: 28.0 parts zinc acrylate, 7.0 parts aluminum methacrylate, 4.0 parts hydroxypropyl acrylate and 2.0 parts octadecyl methacrylate were added to a three-necked reaction flask equipped with a water bath jacket and a stirrer. The mixture was stirred at 225 r / min and heated to 45℃ in a water bath and maintained for 28 min until the material in the flask formed a homogeneous liquid. Heating was stopped and the mixture was cooled to 25℃ to obtain the modified acrylate monomer mixture. It should be used immediately after preparation and stored in a sealed container at 25℃ for no more than 24 h.
[0041] 2) Compounding of environmentally friendly accelerator: The sieved sodium metabisulfite and ascorbic acid are placed in a high-speed mixer at a mass ratio of 4:1 and mixed at 800 r / min for 3 min until the two solids are uniformly distributed; after removal, they are immediately sealed away from light to obtain the environmentally friendly accelerator.
[0042] 3) Compounding of functional inorganic fillers: The sieved nano-silica (D...) is then compounded... 50 The quaternary ammonium salt modified bentonite (200 mesh) and quaternary ammonium salt modified bentonite (25 nm) were added to a conical mixing tank at a mass ratio of 1:2. The mixture was mixed at 400 r / min for 8 min under dry nitrogen protection to obtain a functional inorganic filler, which was then sealed and stored under nitrogen protection.
[0043] 4) Preparation of base component M: Step 1: Add 49.8 parts of deionized water to a 1000 mL stainless steel reactor equipped with a stirrer and a water bath jacket. Turn on the stirrer at 200 r / min. Heat the water bath to 30±2℃. Add 1.6 parts of ethylene glycol monobutyl ether and stir continuously for 5 min until the ethylene glycol monobutyl ether is completely dissolved in the water to form a transparent aqueous solution. Step 2: Keep the stirring speed at 200 r / min and the temperature at 30±2℃, slowly add 32.7 parts of the modified acrylate monomer mixture to the transparent aqueous solution obtained in Step 1 at a dropping rate of 5 mL / min. After the dropping is completed, increase the stirring speed to 350 r / min and continue stirring for 20 min to form a homogeneous monomer aqueous solution. Step 3: Under stirring at 350 r / min, add 3 parts of dehydrated sorbitan monooleate to the monomer aqueous solution obtained in step 2, stir for 5 min, then add 1.5 parts of polyoxyethylene polyoxypropylene ether, stir for 5 min, then add 1.2 parts of environmentally friendly accelerator, stir for 5 min, until the raw materials are completely dissolved and the system is free of particles and stratification. Step 4: Keep the stirring speed at 350 r / min and slowly add 7.3 parts of functional inorganic filler to the system obtained in step 3 at a feeding rate of 1 g / min. After the feeding is completed, increase the stirring speed to 600 r / min, raise the temperature to 35±2℃, and continue stirring for 30 min to achieve the initial dispersion of the filler. Step 5: Add 0.3 parts of hydroxyethyl cellulose (weight average molecular weight 150,000, viscosity of 2% aqueous solution at 25℃ is 1500~2500 mPa·s) to the system obtained in step 4, and stir at 600 r / min for 15 min until the anti-settling agent is completely dissolved and the system is a homogeneous viscous liquid. Step 6: Transfer the above viscous liquid into a colloid mill, adjust the colloid mill gap to 50 μm, grind at 3000 r / min, and grind for 2 cycles. After grinding, check the particle size of the system to ensure that the particle size is ≤50 μm. If the particle size does not meet the standard, add 1 grinding cycle. Step 7: After the grinding is qualified, cool the system to room temperature of 25±5℃, filter it through a 200-mesh filter to remove a small amount of undispersed particles, and obtain the base material component M. Put it into a sealed plastic bucket and store it at room temperature away from light for ≤7 days.
[0044] 2. Preparation of cross-linking component N 1) Preparation of composite crosslinking agent: 6.0 parts of pentaerythritol triallyl ether, 3.0 parts of polyethylene glycol diacrylate and 1.5 parts of N-hydroxymethylacrylamide were added to a glass beaker with a stirrer and stirred at 200 r / min for 15 min at 25℃ until the three raw materials were mixed evenly to obtain the composite crosslinking agent; the composite crosslinking agent was prepared and used immediately and stored in a sealed container at 25℃ for no more than 48 h.
[0045] 2) Compounding of composite initiator: The sieved ammonium persulfate and azobisisobutylamidine hydrochloride are placed in a small mixer at a mass ratio of 4:1. The mixing speed is 500 r / min and the mixing time is 4 min until the solid is completely homogeneous. The composite initiator is obtained by sealing it in a brown bottle and storing it in the dark to avoid high temperature decomposition.
[0046] 3) Initiating the overall preparation of cross-linking component N: Step 1: Add 82.3 parts of deionized water to a 500 mL plastic mixing container with a stirrer, stir at 250 r / min, add 0.2 parts of sodium bicarbonate at 25℃ and continue stirring for 5 min; use a precision pH meter to detect the pH value of the system, and adjust the pH value dropwise to 8.0±0.2 with 0.1 mol / L sodium bicarbonate solution or 0.1 mol / L dilute sulfuric acid; Step 2: Keep the stirring speed at 250 r / min, slowly add 2.8 parts of the composite crosslinking agent to the system obtained in step 1 at a dropping rate of 3 mL / min. After the addition is complete, stir for 12 min to form a homogeneous crosslinking agent aqueous solution. Step 3: Under stirring at 250 r / min, add 10.6 parts of acrylate-butadiene copolymer emulsion (solid content 45.0%, glass transition temperature -22℃, average particle size 200 nm, pH value 8.0) to the crosslinking agent aqueous solution. After adding, increase the stirring speed to 300 r / min and continue stirring for 20 min until the system is free of floating oil and stratification. Step 4: While stirring at 300 r / min, add 2.1 parts of the composite initiator in three portions, each time adding 0.7 parts, with a 3-minute interval between each addition; after the third addition, continue stirring for 10 minutes until the composite initiator is completely dissolved. Step 5: Add 0.2 parts of polydimethylsiloxane to the system obtained in step 4, and stir at 300 r / min for 8 min until there are no obvious bubbles in the system; Step 6: Filter the above system through a 100-mesh filter to remove a small amount of impurities, and obtain the initiating crosslinking component N. Store it in a brown sealed plastic bucket at room temperature away from light for ≤3 days to prevent the initiator from becoming ineffective.
[0047] II. Grouting of Modified Acrylic Composite Grouting Material 1. Pre-construction preparation 1) Check the appearance of the base component M and the crosslinking initiator N to ensure that they are both homogeneous liquids without stratification, precipitation, or clumping. If slight stratification occurs, it can be used normally after stirring at 500 r / min for 10 min. 2) Check whether the two material cylinders, mixing chamber, and grouting pipe of the dual-liquid grouting pump are clean and free of residual impurities, whether the mixing blade in the mixing chamber rotates flexibly, and whether the grouting pipe is unblocked or damaged; 3) The base material component M and the crosslinking initiation component N prepared in step one are respectively loaded into the two raw material tanks of the grouting pump. Dry nitrogen is introduced into the raw material tanks to prevent the system from oxidizing upon contact with air.
[0048] 2. Dynamic mixing The two suction pipes of the grouting pump were inserted into the raw material tanks of the base material component M and the initiating crosslinking component N, respectively. The mass ratio of the grouting pump was set to 1:0.9, that is, when the delivery rate of the base material component M was 10 kg / min, the delivery rate of the initiating crosslinking component N was 9 kg / min. The grouting pump was turned on and run unloaded for 30 s before the raw material delivery was started. The two components were dynamically mixed in the mixing chamber of the grouting pump. The speed of the stirring paddle in the mixing chamber was set to 900 r / min, the effective volume of the mixing chamber was 50 mL, and the residence time of the two components in the chamber was 4 s, resulting in a homogeneous grouting liquid with no obvious phase separation.
[0049] 3. Grouting using building crack sealing technology The grout prepared by the aforementioned method was delivered to the location to be treated, with a crack width of 0.8 mm, through a high-pressure grouting pipe. The initial grouting pressure was 0.3 MPa and maintained for 5 min. After confirming that there was no leakage of grout, the pressure was increased by 0.1 MPa every 5 min. When the pressure reached 0.6 MPa, slight grout overflow appeared on the crack surface, and grouting was stopped. The gel time of the grout at 25°C was 2.8 min.
[0050] 4. Injection effect detection The performance of the mixed slurry and the cured gel was tested. The initial viscosity of the mixed slurry, the compressive strength of the solidified sand, and the permeability coefficient were determined according to JC / T 2037-2010, SY / T 5840-2007, and relevant industry-standard methods. The dry volume retention rate was calculated as follows: the volume of the gel after 24 hours of curing was taken as V0, and it was cured in an environment of 25±2℃ and 50%±5% relative humidity for 7 days. The volume V was then measured. d Dry volume retention rate R=V d / V0×100%, the corresponding drying volume shrinkage rate S=(V0-V d ) / V0×100%=100%-R.
[0051] The results showed that the initial viscosity of the mixed slurry was 62.3 mPa·s, the compressive strength of the solidified sand was 685.4 kPa, the dry volume retention rate was 89.2% (corresponding to a dry volume shrinkage rate of 10.8%), and the permeability coefficient was 3.7 × 10⁻⁶. -9 cm / s, water blocking rate 94.6%, oil blocking rate 8.7%, scour resistance ratio 58 PV, oral LD50 in rats 50 Greater than 10,000 mg / kg.
[0052] Example 2 I. Preparation of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the base component M includes: 41.5 parts of modified acrylate monomer mixture, 7.8 parts of composite hydrophilic and lipophilic regulator, 3.5 parts of environmentally friendly accelerator, 11.2 parts of functional inorganic filler, 33.6 parts of deionized water, 2.4 parts of cosolvent, and 0.6 parts of anti-settling agent; the initiating crosslinking component N includes: 5.9 parts of composite crosslinking agent, 3.2 parts of composite initiator, 18.7 parts of waterborne elastic emulsion, 0.4 parts of pH adjuster, 70.5 parts of deionized water, and 0.17 parts of defoamer; other steps are the same as in Example 1.
[0053] II. Grouting of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the mass ratio of base material component M to initiating crosslinking component N is 1:1.1; the oilfield profile control and water shut-off process is used for injection, the formation temperature is 98℃, the salinity is 92500 mg / L, the injection pressure is 1.3 MPa, and the slurry gel time is 45 s; other steps are the same as in Example 1.
[0054] The grouting effect test results showed that the initial viscosity of the mixed grout was 81.7 mPa·s, the compressive strength of the solidified sand was 752.8 kPa, the dry volume retention rate was 91.5% (corresponding to a dry volume shrinkage rate of 8.5%), and the permeability coefficient was 2.9 × 10⁻⁶. -9 cm / s, water blocking rate 98.3%, oil blocking rate 5.2%, scour resistance ratio 72 PV, oral LD50 in rats 50 Greater than 10,000 mg / kg.
[0055] Example 3 I. Preparation of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the base component M includes: 38.2 parts of modified acrylate monomer mixture, 6.3 parts of composite hydrophilic and lipophilic regulator, 2.4 parts of environmentally friendly accelerator, 9.5 parts of functional inorganic filler, 40.8 parts of deionized water, 2.0 parts of cosolvent, and 0.5 parts of anti-settling agent; the initiating crosslinking component N includes: 4.2 parts of composite crosslinking agent, 2.1 parts of composite initiator, 14.5 parts of water-based elastic emulsion, 0.3 parts of pH adjuster, 77.6 parts of deionized water, and 0.12 parts of defoamer; other steps are the same as in Example 1.
[0056] II. Grouting of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the mass ratio of the base material component M to the crosslinking initiator component N is 1:1.0; the soil and rock reinforcement process is used for grouting, the porosity of the soil and rock is 22%, the grouting pressure is 0.9 MPa, and the grout gelation time is 1.7 min; the other steps are the same as in Example 1.
[0057] The grouting effect test results showed that the initial viscosity of the mixed grout was 73.5 mPa·s, the compressive strength of the solidified sand was 718.6 kPa, the dry volume retention rate was 90.3% (corresponding to a dry volume shrinkage rate of 9.7%), and the permeability coefficient was 3.2 × 10⁻⁶. - 9 cm / s, water blocking rate 96.8%, oil blocking rate 6.9%, scour resistance ratio 65 PV, oral LD50 in rats 50 Greater than 10,000 mg / kg.
[0058] Example 4 I. Preparation of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the base component M includes: 29.4 parts of modified acrylate monomer mixture, 3.8 parts of composite hydrophilic and lipophilic regulator, 0.9 parts of environmentally friendly accelerator, 6.1 parts of functional inorganic filler, 56.2 parts of deionized water, 1.3 parts of cosolvent, and 0.2 parts of anti-settling agent; the initiating crosslinking component N includes: 2.1 parts of composite crosslinking agent, 0.9 parts of composite initiator, 9.2 parts of water-based elastic emulsion, 0.2 parts of pH adjuster, 82.3 parts of deionized water, and 0.07 parts of defoamer; the internal proportions of each composite raw material and other preparation steps are the same as in Example 1.
[0059] II. Grouting of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the mass ratio of base material component M to crosslinking initiator component N is 1:0.8; the microcrack sealing process is used for grouting, the crack width is 0.5 mm, the grouting pressure is 0.4 MPa, and the grout gel time is 4.2 min; the other steps are the same as in Example 1.
[0060] The grouting effect test results showed that the initial viscosity of the mixed grout was 55.8 mPa·s, the compressive strength of the solidified sand was 653.9 kPa, the dry volume retention rate was 87.6% (corresponding to a dry volume shrinkage rate of 12.4%), and the permeability coefficient was 4.1×10⁻⁶. - 9 cm / s, water blocking rate 93.2%, oil blocking rate 9.5%, scour resistance ratio 52 PV, oral LD50 in rats 50 Greater than 10,000 mg / kg.
[0061] Example 5 I. Preparation of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the base component M includes: 46.8 parts of modified acrylate monomer mixture, 8.5 parts of composite hydrophilic and lipophilic regulator, 3.9 parts of environmentally friendly accelerator, 12.1 parts of functional inorganic filler, 34.7 parts of deionized water, 2.6 parts of cosolvent, and 0.7 parts of anti-settling agent; the initiating crosslinking component N includes: 6.5 parts of composite crosslinking agent, 3.7 parts of composite initiator, 19.2 parts of water-based elastic emulsion, 0.5 parts of pH adjuster, 68.9 parts of deionized water, and 0.19 parts of defoamer; the internal proportions of each composite raw material and other preparation steps are the same as in Example 1.
[0062] II. Grouting of Modified Acrylic Composite Grouting Material The difference from Example 1 is that the mass ratio of base material component M to initiating crosslinking component N is 1:1.2; high temperature and high salinity oilfield water shut-off injection is used, the formation temperature is 115℃, the salinity is 98700 mg / L, the injection pressure is 1.4 MPa, and the slurry gelation time is 38 s; other steps are the same as in Example 1.
[0063] The grouting effect test results showed that the initial viscosity of the mixed grout was 88.4 mPa·s, the compressive strength of the solidified sand was 786.3 kPa, the dry volume retention rate was 92.7% (corresponding to a dry volume shrinkage rate of 7.3%), and the permeability coefficient was 2.5 × 10⁻⁶. - 9 cm / s, water blocking rate 99.1%, oil blocking rate 4.5%, scour resistance ratio 78 PV, oral LD50 in rats 50 Greater than 10,000 mg / kg.
[0064] In summary, Examples 1-5 all adopted the aforementioned raw material ratio range and preparation process. The initial viscosity of the mixed slurry was 55.8-88.4 mPa·s, the compressive strength of the solidified sand was 653.9-786.3 kPa, the dry volume retention rate was 87.6%-92.7% (corresponding to a dry volume shrinkage rate of 7.3%-12.4%), and the permeability coefficient was 2.5×10⁻⁶. -9 ~4.1×10 -9 cm / s, water blocking rate 93.2%~99.1%, oil blocking rate 4.5%~9.5%, scour resistance ratio 52~78 PV, oral LD50 in rats 50 All values were greater than 10,000 mg / kg. These results demonstrate that the formulation exhibits reproducible overall performance at the listed dosage points, and the gel time can be adjusted by varying the mixing ratio of the base component M to the initiating crosslinking component N, as well as the dosage of the composite initiator, to adapt it to applications such as building seepage prevention and plugging, soil and rock reinforcement, and oilfield profile control and water shut-off. The existing data are used to illustrate the overall feasibility and performance of the composite formulation and should not be considered as single-factor causal evidence of the irreplaceability of any single component.
[0065] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of this invention.
Claims
1. A modified acrylic composite grouting material, characterized in that, Including base component M and initiating crosslinking component N, by weight, The base component M includes: 28-54 parts of modified acrylate monomer mixture, 3.2-8.9 parts of composite hydrophilic and lipophilic modifier, 0.6-4.1 parts of environmentally friendly accelerator, 5.7-12.5 parts of functional inorganic filler, 32.8-56.9 parts of solvent, 1.1-2.7 parts of co-solvent and 0.2-0.7 parts of anti-settling agent; The cross-linking initiating component N includes: 1.5~10.5 parts of composite cross-linking agent, 0.7~3.9 parts of composite initiator, 8.5~19.6 parts of aqueous elastic emulsion, 0.1~0.5 parts of pH adjuster, 68.9~82.3 parts of solvent and 0.05~0.2 parts of defoamer; The modified acrylate monomer mixture comprises 20-35 parts zinc acrylate, 5-10 parts aluminum methacrylate, 2-6 parts hydroxypropyl acrylate, and 1-3 parts octadecyl methacrylate; the composite hydrophilic and lipophilic regulator comprises sorbitan monooleate and polyoxyethylene polyoxypropylene ether in a mass ratio of 2:1; the environmentally friendly accelerator comprises sodium metabisulfite and ascorbic acid in a mass ratio of (3-5):1; the functional inorganic filler comprises nano-silica and modified bentonite in a mass ratio of 1:2; the composite crosslinking agent comprises 4-7 parts pentaerythritol triallyl ether, 2-5 parts polyethylene glycol diacrylate, and 1-2 parts N-hydroxymethylacrylamide; and the composite initiator comprises ammonium persulfate and azobisisobutylamidine hydrochloride in a mass ratio of 4:
1.
2. The modified acrylic composite grouting material according to claim 1, characterized in that, The modified bentonite is bentonite modified with quaternary ammonium salt.
3. The modified acrylic composite grouting material according to claim 1, characterized in that, The solvent is water.
4. The modified acrylic composite grouting material according to claim 1, characterized in that, The co-solvent is selected from one or more of ethylene glycol monobutyl ether, propylene glycol methyl ether, and diethylene glycol monobutyl ether.
5. The modified acrylic composite grouting material according to claim 1, characterized in that, The anti-settling agent is selected from one or more of hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, and xanthan gum.
6. The modified acrylic composite grouting material according to claim 1, characterized in that, The aqueous elastic emulsion is selected from one or more of acrylate-butadiene copolymer emulsion, pure acrylic emulsion, styrene-acrylic emulsion, and carboxylated styrene-butadiene emulsion.
7. The modified acrylic composite grouting material according to claim 1, characterized in that, The pH adjuster is selected from one or more of sodium bicarbonate, potassium bicarbonate, and sodium carbonate.
8. The modified acrylic composite grouting material according to claim 1, characterized in that, The defoamer is selected from one or more of polydimethylsiloxane and polyether-modified siloxane.
9. The preparation method of the modified acrylic composite grouting material according to any one of claims 1 to 8, characterized in that, 20-35 parts zinc acrylate, 5-10 parts aluminum methacrylate, 2-6 parts hydroxypropyl acrylate, and 1-3 parts octadecyl methacrylate are mixed to obtain a modified acrylate monomer mixture; sodium metabisulfite and ascorbic acid are mixed at a mass ratio of (3-5):1 to obtain an environmentally friendly accelerator; sieved nano-silica and modified bentonite are mixed at a mass ratio of 1:2 to obtain a functional inorganic filler; under stirring, the co-solvent, the modified acrylate monomer mixture, the composite hydrophilic and lipophilic regulator, the environmentally friendly accelerator, the functional inorganic filler, and the anti-settling agent are dissolved in the solvent in sequence, ground, and filtered to obtain the base component M; 4-7 parts of pentaerythritol triallyl ether, 2-5 parts of polyethylene glycol diacrylate, and 1-2 parts of N-hydroxymethylacrylamide were mixed to obtain a composite crosslinking agent; ammonium persulfate and azobisisobutylamidine hydrochloride were mixed at a mass ratio of 4:1 to obtain a composite initiator; under stirring, a pH adjuster, a composite crosslinking agent, an aqueous elastic emulsion, a composite initiator, and an antifoaming agent were dissolved in a solvent in sequence, filtered, and the initiating crosslinking component N was obtained.
10. A grouting method for the modified acrylic composite grouting material according to any one of claims 1 to 8, characterized in that, The base material component M and the crosslinking initiator component N are mixed at a mass ratio of 1:(0.8~1.2) and then injected into the grouting location using a staged pressurization method.